2013
DOI: 10.3109/00207454.2013.789513
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-based therapy: a new dimension in epilepsy treatment

Abstract: Epilepsy is a brain disorder, which is characterized by a predisposition to generate seizures that are associated with neurobiological, psychological cognitive and linguistic problems. Current treatments of epilepsy remain difficult, and antiepileptic drugs fail for some patients. Expressions of different microRNAs (miRNAs) in different brain regions are implicated in epileptogenic activity. MiRNAs are important regulators of seizure-induced neuronal death. The activation of inflammatory pathways is involved i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 60 publications
0
6
0
Order By: Relevance
“…However, the mechanism of cognitive impairment is not clear. Studies on epilepsy have shown that cognitive impairment is dependent on the degree of microglial activation and inflammation (Otte et al, 2012;Liu et al, 2013), possibly involving proinflammatory cytokines (e.g. TNF-α and IL-6).…”
Section: Discussionmentioning
confidence: 99%
“…However, the mechanism of cognitive impairment is not clear. Studies on epilepsy have shown that cognitive impairment is dependent on the degree of microglial activation and inflammation (Otte et al, 2012;Liu et al, 2013), possibly involving proinflammatory cytokines (e.g. TNF-α and IL-6).…”
Section: Discussionmentioning
confidence: 99%
“…Micro RNA (MiRs) have also emerged as key players that regulates seizure‐induced neuronal death and the innate immune response in the modulation of astrocyte‐mediated inflammation (Liu et al . ). In an experimental model of autoimmune encephalomyelitis (AE)‐related epilepsy, MiRs‐129‐5p prevents the development of AE‐related epilepsy via targeting HMGB1 expression and inhibiting TLR4/NF‐kB signaling axis.…”
Section: Hmgb1‐targeting Therapeutic Agents In Epilepsy: An Updatementioning
confidence: 97%
“…A BBB-penetrating small molecule inhibitor may provide an advantage over the use of siRNA to modulate FTO. Similarly, this approach may have an advantage over antagomir-based methods to modulate miRNA that have been proposed for the treatment of epilepsy . While we cannot definitively state at this time that the inhibition of FTO is the cause of the anticonvulsant activity and of the modulation of miRNA, there is considerable emerging discussion describing a functional, interdependent role of these activities.…”
Section: Discussionmentioning
confidence: 99%